The Effectiveness of Information Technology-Based Student Entrepreneurship Competencies in Islamic Boarding Schools - Arief Hendra Kurniawan; Purwanto Purwanto; Muhammad Munadi; Ida Royani (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
This study aims to determine the effectiveness of the competence of students based on information technology. This research is a qualitative research case study model (case study). The study was conducted by direct observation and in-depth interviews at the IT Yogyakarta Islamic Boarding School. Observations were made during information technology-based learning from marketer, multimedia, and programmer programs. Then an open interview was conducted to obtain data on the digital effectiveness of the students' competence. The results of in-depth observations and interviews in this study indicate that the use of information technology as the main learning in addition to learning religious knowledge is very effective in helping students benefit when they enter the community. Information technology-based competencies increase income when entering the entrepreneurial world or become a plus when working in the e-commerce world.